1984
DOI: 10.2307/1939121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microtopography and Canopy Species on Spatial Patterns of Forest Understory Plants

Abstract: In a maple-beech forest in eastern New York, equal numbers of mounds, pits, and adjacent undisturbed soil microsites were censused for plant species density and cover over the growing seasons of 1978 and 1979. Several soil properties were also measured for each microsite. Detrended correspondence analysis (DCA) and chi-square goodness-of-fit tests were used to test whether the species were uniformly distributed over the microrelief positions. Comparisons of species composition, diversity, and vegetative phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
328
6
5

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 463 publications
(354 citation statements)
references
References 35 publications
15
328
6
5
Order By: Relevance
“…We have shown that substrate moisture influences seed germination velocity, although it does not affect overall percentage germination. Consequently, in somewhat drier microsites (e.g., on small mounds, a topographic feature common in temperate forests; Beatty, 1984), seeds may thus germinate later in the fall; seedlings from such seeds may emerge later the following spring, have a shorter longevity, and not have the time to mature seeds (Smith, 1983c). The results of our litter experiment showed that few seedlings emerge from under a thick leaf litter.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that substrate moisture influences seed germination velocity, although it does not affect overall percentage germination. Consequently, in somewhat drier microsites (e.g., on small mounds, a topographic feature common in temperate forests; Beatty, 1984), seeds may thus germinate later in the fall; seedlings from such seeds may emerge later the following spring, have a shorter longevity, and not have the time to mature seeds (Smith, 1983c). The results of our litter experiment showed that few seedlings emerge from under a thick leaf litter.…”
Section: Discussionmentioning
confidence: 99%
“…Low and higher elevation sites have markedly different soil characteristics, with lowland soils having higher fertility, levels of organic matter, and water availability, factors that could potentially influence the AM fungal community and the inoculum potential Robson 1991, Brundrett 1991). Because soil biogeochemical characteristics, including pH, level of organic matter, and mineral element concentrations are also influenced by the dominant tree species (Beatty 1984, Boerner and Koslowsky 1989, Finzi et al 1998a, we also tested whether inoculum potential varied depending on the host tree species dominating the soil patch.…”
Section: Introductionmentioning
confidence: 99%
“…‱ Plants should be aggregated and associated to nutrient-rich patches if they are nutrient-limited [58,15].…”
Section: Spatial Patterns Of Tree Speciesmentioning
confidence: 99%